2003
DOI: 10.1179/027249303322296510
|View full text |Cite
|
Sign up to set email alerts
|

Delayed visual maturation in Karen refugee infants

Abstract: Thirty-eight babies born to Karen mothers living in camps for displaced persons in north-western Thailand have delayed visual maturation (DVM type 1) that recovers within 6 months. Vitamin A concentrations were deficient in 16% of breast-milk samples from lactating mothers and vitamin B(1) concentrations were deficient in 60% of plasma samples. Infantile beriberi was common in this population. The levels of fatty acids in plasma and milk in Karen women were excellent at birth and in the postpartum period. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Among the infants on the Thailand/Burma border, McGready et al [50] demonstrated delayed visual maturation type 1 and suggested thiamin deficiency as a possible cause. Follow up of Israeli infants who survived beriberi, due to substandard infant formula devoid of thiamin, suggests that thiamin deficiency was associated with subsequent delayed language development and epilepsy [51].…”
Section: Discussionmentioning
confidence: 99%
“…Among the infants on the Thailand/Burma border, McGready et al [50] demonstrated delayed visual maturation type 1 and suggested thiamin deficiency as a possible cause. Follow up of Israeli infants who survived beriberi, due to substandard infant formula devoid of thiamin, suggests that thiamin deficiency was associated with subsequent delayed language development and epilepsy [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, in those with various degrees of maternal illness and/or malnutrition, differences are much more marked. The extent to which these are the reflection of the ethnic background and are the main contributing factors remains unsolved [McGready et al, 2000[McGready et al, , 2003. However, in these circumstances the neurological examination is often used to compare groups of infants and thus it remains a useful tool.…”
Section: Cautions and Limitationsmentioning
confidence: 99%
“…Therefore, CNS development in an environment that lacks thiamine will probably be negatively affected [47,33]. Although cerebral plasticity enables the compensation of the vitamin shortcoming, the molecular mechanism and its limit of action are still unknown.…”
Section: Thiamine Shortcoming and Damage To Cognitive Developmentmentioning
confidence: 99%